The effect of the clinical supervision model on nursing internship students' nursing process-based performance: an experimental study - Amir Shahzeydi; Sedigheh Farzi; Mohammad Javad Tarrahi; Fakhri Sabouhi; Sima Babaei; Ahmadreza Yazdannik (BMC, 2024)
Abstract Background The nursing process is a systematic method for identifying the patient's problems and planning to resolve them. It is also a crucial pillar of high-quality nursing care. Nursing internship students may lack the necessary skills to implement the nursing process due to the increased independence, the absence of constant professorial supervision, and limited experience. The clinical supervision model is a method of clinical education that bridges the gap between theory and practice. Objective This study was conducted to investigate the impact of the clinical supervision model on the performance of nursing internship students in each of the five stages of the nursing process, as well as overall. Method This experimental study was conducted in 2022. The 70 eligible internship students were conveniently selected and randomly assigned to either an intervention or a control group. In the present study, the clinical supervision model was implemented for the intervention group, while the control group received routine supervision. This was carried out over six sessions in three months. The data collection was conducted using a researcher-developed checklist of nursing process-based performance in both groups. Moreover, the Manchester questionnaire was used to evaluate the model in the intervention group. The variables considered as confounding factors included age, gender, marital status, number of monthly shifts, and grades of the nursing process credit completed in the third semester. SPSS version 16 software, descriptive statistics (frequency distribution, percentage, mean, and standard deviation), and analytical statistics (independent t-test, chi square, repeated measures Anova and LSD) were used to analyze the data. Results Intergroup analysis revealed that there was no significant difference between the scores of nursing process steps and the total score before the intervention in the control and intervention groups, as well as in baseline characteristics (P > 0.05). According to the intragroup analysis, the intervention group showed a significant increase in both the total scores and scores of nursing process steps over time (P < 0.001), whereas the control group exhibited contradictory results (P > 0.05). Finally, the "P-Value Intervention" demonstrated the effectiveness of this training model in improving the performance of the intervention group based on the nursing process compared to the control group. The mean score of the Manchester questionnaire in the intervention group was 136.74, indicating the high impact of implementing the clinical supervision model in the intervention group. Conclusion The results indicated that the implementation of the clinical supervision model led to improved utilization of the nursing process by nursing internship students at all stages. Therefore, it is recommended that nurse educators utilize the clinical supervision model by providing feedback on errors in action during supervision sessions to enhance the quality of nursing care provided by nursing internship students and improve patient safety in clinical environment.